PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN PROVINSI SULAWESI TENGAH - Ismiralda, Ismiralda (Katalogis, 2017)
This research intends to: determine and analyze simultaneous and partial influence of transformational leadership style, work motivation and organizational culture on officials’ performance in The Department of Transportation Central Sulawesi province. Sample in this research consists of 93 officials in The Department of Transportation Central Sulawesi Province. The results show that: transformational leadership, work motivation and organizational culture simultaneously and partially have significant influence on officials’ perfomance in The Department of Transportation Centar Sulawesi Province.